ASSESSMENT OF BUSINESS MODEL TRANSFORMATION TOWARD A PRODUCT-SERVICE SYSTEM AT TOKO ROTI ENAK, SOUTH TANGERANG - Rossikhasanah Ummaiyah Habibah; Nanang Alamsyah; Mohammad Rachman Waluyo; Wendy Febrianty Mardhiyah (Journal of Business Studies and Management Review, 2025)
This study examines the transformation of Toko Roti Enak, South Tangerang branch, toward a Product-Service System (PSS) based business model by analysing the opportunities offered through Quadrant 2 (Product Related Service) and Quadrant 4 (Product Related Software). The research employs a qualitative-descriptive approach supported by interviews and direct observations to understand the bakery’s current conditions and its potential to integrate service and digital innovations. The findings show that implementing Product Related Service can enhance customer experience through additional offerings such as delivery services, pre-order systems, loyalty programmes, and product consultation. These service enhancements are expected to strengthen customer engagement, improve convenience, and support long-term loyalty. Meanwhile, the application of Product Related Software provides opportunities to modernise operational processes through the use of ordering applications, CRM systems, digital stock management, and integrated cashier databases. These technological tools contribute to more efficient workflows, reduced operational errors, and data-driven decision-making. The combined implementation of both quadrants indicates that Toko Roti Enak can create a more integrated, customer-focused, and digitally adaptive business model. The adoption of the PSS approach not only improves service quality and operational performance but also strengthens the bakery’s competitiveness and supports sustainable growth in the increasingly digitalised F&B sector.